Uji Kesyariahan Akad Murabahah pada Produk Pembiayaan Bank Sumut Syariah Kcp Kota Baru Marelan - Iswanty, Widya; Jannah, Nurul (Regress: Journal of Economics & Management, 2022)
Banks are financial institutions that have a very important role in developing the country's economy. In the banking world, there is a dual banking system known in the community as conventional banking and Islamic banking. Islamic banks are banks that operate in accordance with sharia principles or banks whose operating procedures refer to the Koran and al-hadith. One of the contracts in Islamic banking products is the Murabaha contract. Murabahah contract is a financing contract that is most often used by banks because it has a low risk. In order for a murabahah contract to be like sharia principles, there must be two separate buying and selling transactions. First, namely transactions between suppliers and banks, this is done before the second transaction takes place, namely transactions between banks and customers. These two transactions are unavoidable in order to comply with sharia principles.